Super volcanoes : what they reveal about Earth and the worlds beyond - Andrews, Robin George (W.W. Norton & Company, 2022)
"An exhilarating, time-traveling journey to the solar system's strangest and most awe-inspiring volcanoes. Volcanoes are capable of acts of pyrotechnical prowess verging on magic: they spout black magma more fluid than water, create shimmering cities of glass at the bottom of the ocean and frozen lakes of lava on the moon, and can even tip entire planets over. Despite their reputation for destruction, volcanoes are inseparable from the creation of our planet. Super Volcanoes revels in the incomparable power of volcanic eruptions past and present, Earth-bound and otherwise, and explores how these eruptions reveal secrets about the worlds to which they belong. Science journalist and volcanologist Robin George Andrews describes the stunning ways in which volcanoes can sculpt the sea, land, and sky, and even influence the machinery that makes or breaks the existence of life. Traveling from Hawaii, Tanzania, Yellowstone, and the ocean floor to the moon, Venus, and Mars, Andrews explores cutting-edge discoveries and lingering scientific mysteries surrounding these phenomenal forces of nature"--